Ukraine : Selected Issues. (IMF Staff Country Reports; Country Report, 2008)
This Selected Issues paper analyzes the Ukrainian business cycle. It focuses on the price of steel-Ukraine's major export-and its relation to the economic performance. It establishes a forecasting model for steel prices, which points to downside risks to steel prices. It discusses the effects of steel price fluctuations on economic activity and how policies might then mitigate them. The paper also develops core inflation indicators for Ukraine to better distinguish underlying from temporary influences on inflation.